Fósforo em Planossolo cultivado com culturas de sequeiro e sua disponibilidade para o arroz subsequente em Plantio Direto. - Fortes, Magali de Ávila (2009)
The general objective of this study was to evaluate the effect of the phosphorus fertilization and the availability of the phosphorus forms in irrigated rice under no tillage in Albaqualf soil cultivated on dryland crops mulch. The experiments installed in 2003 were conducted under a randomized blocks design with four replications. The treatments were disposed in 2 x 2 factorial (triple superphosphate - TSP) and Arad rock phosphate (ARP), with and without annual replication of P with TSF). Additionally, it was conducted a treatment under natural condition (without the application of the phosphorus fertilization). The soils collected from the layers: 0 - 10 cm and 0 - 20 cm were analyzed using the Mehlich-1 and anion-exchange resin methods. Soils collected from 0.0 - 2.5; 2.5 - 5.0 and 5.0 - 15.0 cm was used to evaluate the P fractions. Analysis of P concentration in flag leaves and shoot (leaves stalk and grain) were also evaluated. Total P accumulated was calculated from the shoot P concentration in relation to the dry matter. For the future analysis, the rice harvest was done when the plants were in physiological maturity stage. The phosphorus fertilization did not affect the production of rice grains; even though with initial P soil level below of the critical level (< 6.0 mg dm-3). The phosphorus fertilization applied to the dryland crops (maize and soybean) presented a residual effect to subsequent irrigated rice, even after four years of experiment under notillage management. For the irrigated rice no differences were shown between the results of P availability using the Mehlich-1 and anion-exchange resin methods. The P concentrations from the soils, using these two methods, presented significant correlations with the P accumulated in plants. The ARP presented similar performance as TSP regarding to the P nutrition in irrigated rice in rotation with dryland crops under no tillage. The P inorganic fractions that predominate in Albaqualf soil cultivated with maize and soybean under no tillage are extracted with 0.1 NaOH and 0.5 NaOH mol L-1. The fertilizations carried out annually with TSP and ARP had increased all the P inorganic fractions in soil. The organic fractions were not much affected by the phosphate fertilization. The P accumulated in shoot of rice plants was better correlated with the labile P fractions (anion-exchange resin, NaHCO3 and 0.1 NaOH mol L-1), mainly in the superficial layer (0.0 - 2.5 cm).